Prisoner, prison and situational characteristics and their relationship with the prevalence, incidence and type of prison offending recorded by a sample of prisoners within Western Australian prisons - Phillips, Catharine (2019)
The importance that researchers and prison administrators have placed on ensuring that the good governance, security and safety of prisons are maintained has generated a number of studies of prison offending. Previous studies have identified several prisoner, prison and situational characteristics as relevant in regard to their relationship with the prevalence, incidence and type of prison offences committed. However, no studies have been conducted in Australia, and therefore no studies have included Aboriginal prisoners in their prisoner samples. In addition, the differences in regard to legislation pertaining to prison offending between jurisdictions is also of importance when considering the generalisability of the body of research available on the subject. The present study involved the examination of the relationship between several prisoner and prison characteristics and the prevalence and incidence of prison offending, and several prisoner, prison and situational characteristics and the types of prison offences committed by male, female, Aboriginal and non-Aboriginal prisoner samples. The prevalence, incidence and type of prison offences were examined within and across all adult prison facilities in Western Australia, and included all adult prisoners who had spent the full 12-month study period in prison within Western Australia. Logistic regression and multiple regression analyses revealed that several prisoner and prison characteristics were significantly related to with the prevalence and incidence of prison offending, while logistic regression analyses revealed that several prisoner, prison and situational characteristics were significantly related to the type of prison offences committed by male, female, Aboriginal and non-Aboriginal prisoners included in the prisoner sample. The present study provides a useful addition to the existing body of research due to it being the first of its kind to include Aboriginal prisoners in an Australian context. The present study also provides generalisable findings to other Australian prisoner populations, and may prove to be of practical importance to other Australian jurisdictions, particularly those where the overrepresentation of Aboriginal people is of an extent similar to that of Western Australia. Practical interventions informed by the findings of the present study may help to reduce the prevalence and incidence of prison offending, and the severity of such offending, which may subsequently improve the security of prisons, the safety of staff, prisoners and visitors, and reduce the financial implications for prison systems, governments and taxpayers in respect of compensation for injured prison staff, prisoners or visitors, costs associated with the rectification of damage caused by prisoners, and costs associated with the administrative processes relating to the progression of formal prison charges